PERANAN PEMERINTAH KOTA YOGYAKARTA DALAM MENINGKATKAN PELAYANAN PERIZINAN DAN MEWUJUDKAN FUNGSI IZIN SEBAGAI ALAT PENGENDALI BAGI KEGIATAN MASYARAKAT YANG MEMBAHAYAKAN LINGKUNGAN - Nurwigati, Nurwigati (Jurnal Media Hukum, 2010)
The research aims to discover the relation between debureaucratization of licensing service and actualization of license function as a control to societyâs threatening activities in order to avoid vicinityâs threats. The research resulted in some points, as licensing service in Yogyakarta municipality is not only quick, simple, and transparent, but also makes environmental aspect as one of its main concerns. Since documents in environmental management become main requirement to attain the license, when Environmental Bureau decides that all required in UKL-UPL, DPL has been completed, this bureau will issue the license no longer than 3 days. It is expected that the license will be processed exactly as the allocated time.Â  Meanwhile, in relation with retribution fee on making the license, the fee will be paid to Financial Management Board and then used it in preventing environmental threats via Environmental Service. Total budget available for this program is IDR. 11,353,434.740; on the other hand, income from retribution fee on licensing in 2007 was IDR. 2,216,475.050. It means that all the income from retribution fee on licensing returns back to society to prevent vicinityâs threats, even the municipality still provides additional funds from its budget.Keywords: Debureaucratization, Licensing Service, Environment.